The Influence of Digital Literacy and Learning Styles on Student Academic Achievement (Case Study: Gen Z Students in Asahan Regency) - Delvia Eka Syafitri; Ulfa Aulia Harahap (PT Bukuloka Literasi Bangsa, 2026)
Abstract This study aims to analyze the influence of digital literacy and learning styles on the academic achievement of Gen Z students in Asahan Regency. Rapid developments in digital technology require students to have good digital literacy skills and appropriate learning styles in order to achieve optimal academic performance. This study uses a quantitative approach with a survey method. The research population consisted of all Gen Z students in Asahan Regency, with a simple random sampling technique used. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was performed using multiple linear regression analysis with the help of statistical programs. The results showed that digital literacy had a positive but insignificant effect on student academic achievement. In addition, learning style also has a positive and significant effect on student academic achievement. Simultaneously, digital literacy and learning style have a significant effect on the academic achievement of Gen Z students in Asahan Regency. This study is expected to be taken into consideration by educational institutions in improving student academic achievement through strengthening digital literacy and developing effective learning styles. Keywords: Digital Literacy, Learning Style, Academic Achievement, Gen Z Students